Research methods used in the production of knowledge on nursing administration - Abel Silva de Meneses; Maria Cristina Sanna (Universidade Federal de Goias, 2015)
This study aimed to analyze and describe the characteristics of research methods used in the production of dissertations and theses on Nursing Administration. This is a documentary study of quantitative approach, covering 596 abstracts of research works on Nursing Administration, analyzed according to the variables of research method, temporal distribution, titles and themes. Of all analyzed abstracts, 49.8% were quantitative studies and 43.1% were qualitative. Descriptive studies amounted to 74.8%, exploratory to 21.5% and cross-sectional accounted for 86.7%. As for the data collection procedure, 46.8% were case studies and 25.7% were surveys. The positivist thought guided 49.0% of studies and phenomenology appeared in 19.3%. Only 38.3% of the studies deepened the analysis with the philosophical and theoretical framework. We concluded that the Nursing Administration knowledge was predominantly formed by quantitative, descriptive, cross-sectional and case studies, enlightened by the positivist thought and of little depth in the philosophical and theoretical framework of analysis.